A retrospective study of risk factors for prolonged mechanical ventilation after coronary artery bypass grafting (CABG) surgery in Hospital Universiti Sains Malaysia Kubang Kerian Kelantan - Hariri, Firman (2015)
INTRODUCTION Prolonged mechanical ventilation after CABG surgery increases airway and lung trauma ultimately increases hospitalization costs. It is well documented that the main clinical advantages of early extubation are reduced likelihood the adverse effects of positive pressure ventilation and minimized of associated patient discomfort, a potential decrease in infection and early ambulation. Many has attempted in promoting early extubation as a mean to reducing intensive care and hospitalization costs. A few models have been developed aim to identify patients at risks of PMV. Some studies attempted to compare those prediction models developed in the ICU. The main objective of this study is to identify patient characteristics and operative variables that predict PMV in patients undergoing coronary artery bypass grafting (CABG). The record of patients who underwent CABG from January 2009 to December 2013 will be examined retrospectively. These patients will be divided into normal and prolonged mechanical ventilation (PMV) groups. Putative factors affecting the durationof intubation will be included in univariate analysis and subsequently run into logistic regression model to determine the risk factors associated with PMV. There were numerous studies that had successfully predicted the risks and established a risk models. We attempt to study those putative characteristics and variables in a relatively small cardiothoracic unit whereby patients population were more homogenous and operated by a single surgeon at Hospital Universiti Sains Malaysia (HUSM) and compare previously considered risk factors. METHODOLOGY It is a retrospective cohort analysis of patient’s case notes in Cardiothoracic Surgery Unit of Hospital University Sains Malaysia, Kubang Kerian Kelantan. All patients who had undergone elective isolated CABG between January 2009 and December 2013 are traced. A computer generated list will be obtained from medical record office. The cases are identified according to T-codes of the international classification of disease-Tenth revision (ICD-10). Sampling frame is obtained and all patients fulfilling the inclusion and exclusion criteria were recruited. Selected perioperative characteristics data will be collected by reviewing traced medical records. Keywords used when retrieving records is coronary artery bypass grafting or CABG. Statistical analysis was done using SPSS software version 22.0. RESULTS There were 140 patients enrolled, only twenty four patients required prolonged mechanical ventilation (PMV) of more than 24 hours. This made the incidence of 17.1%. Male gender contributed to the majority of the PMV group 91.7%. This percentage however did not reflect the true gender distribution as the number of female population in the study was only 19 and only 2 fall into the PMV group. Perioperative univariate analysis showed that renal dysfunction (20.8% versus 3.4%; p = 0.05), NYHA class IV (37.5% versus 6.9%; p < 0.01), recent MI (58.3% versus 12.9%; p < 0.01), LVEF < 30% (16.7% versus 4.3%; p = 0.037), preoperative PaCO2 (35.0 versus 39.2; p = 0.113), cardiopulmonary bypass time (136 minute versus 126 minute; p = 0.175), intraoperative blood transfusion (925 ml versus 831 ml; p = 0.24), post operative cardiac arrhythmias (37.5% versus 12.1%; p = 0.004), post operative acute renal failure (33.3% versus 1.7%; p < 0.001) and post operative hemorrhage (58% versus 4.3%; p < 0.001) were significant. In multiple logistic regression analysis, study demonstrates renal dysfunction (OR = 12.90; 95% CI 1.33-124.99), advance NYHA class IV (OR = 7.10; 95% CI 1.33-37.93), recent MI (OR = 8.12; 95% CI 1.81-36.38) and postoperative hemorrhage (OR = 25.1; 95% CI 4.73-132.76) were found to be independent risk factors associated with PMV after CABG surgery. The study also demonstrates significant higher length of hospital stay in PMV group. For 1 day additional hospital stay, it increases the risk of PMV by 1.18 times (95% CI 1.05-1.31) when adjusted to other factors. CONCLUSION Prolonged mechanical ventilation after CABG surgery is associated with the presence of existing renal dysfunction, NYHA class IV, recent myocardiac infarction and post operative hemorrhage. Those patients who require prolonged ventilation have significantly higher hospital stay.